Senegal : Financial Depth and Macrostability - Imam, Patrick (Departmental Papers; Departmental Paper, 2013)
This enhanced review of Senegal's financial sector is one of several pilot reviews called for by the Executive Board in May 2012. The purpose of the reviews is to go beyond the traditional surveillance focus on banking system soundness and solvency by analyzing in more depth the interplay between financial development, macroeconomic and financial stability, and effectiveness of macroeconomic policies in low-income countries. Senegal is a member of the West African Economic and Monetary Union; a number of key macroeconomic and financial policies are designed and implemented at the union level. This study focuses on Senegal-specific issues. Another pilot study, to be prepared in the context of the next annual consultation on regional policies in early 2013, will focus on union-wide issues.